Consumer Trust as a Mediator of the Link Between Promotional Mix and Customer’s Decision to Use Cellular Phone Service - Al-Qadasi, Ahmed; Karim, Fazida (Archives of Business Research, 2023)
Customer’s (use) purchasing decision making have the crucial point of several marketing decision-makers in all type of businesses. Studies have suggested that ambiguity still exist in terms of variables capable of enhancing the indirect link between the promotional mix (PM) and customer’s purchasing (use) decision, specifically in the cellular communication sectors of most of the developing countries. This study is an attempt to explore the link between promotional mix (PM), consumer trust, and customer use decisions in the context of Yemen cellular communications sector. The hierarchy of effects theory is used as underlying theory, and quantitative cross-sectional survey method with questionnaire were used in collecting data. The random sampling method was used in distributing the questionnaire to 382 respondents . The Partial Least Squares Structural Equation Modelling (PLS-SEM) was used in analyzing the data. The result shows that promotional mix and customer trust has significant and positive effect on customer use decisions, and customer trust mediate the link between promotion mix and customer use decisions. Finally, the study provided some useful suggestions for future studies.